Sociobiome signals by high income for increased mobile genetic elements in the gut microbiome of Chinese individuals - Tian, Chen; Zhang, Zhigang (Frontiers in Microbiology, 2025)
IntroductionMobile genetic elements (MGEs) play a crucial role in the dissemination of antibiotic resistance genes (ARGs), posing significant public health concerns. Despite their importance, the impact of socioeconomic factors on MGEs within the human gut microbiome remains poorly understood.MethodsWe reanalyzed 1,382 publicly available human gut metagenomic datasets from Chinese populations, including 415 individuals from high-income eastern regions and 967 individuals from low- and middle-income western regions. MGEs were identified and categorized into functional groups, and statistical analyses were conducted to assess regional differences and correlations with economic indicators.ResultsA total of 638,097 nonredundant MGEs were identified. Among these, MGEs related to integration/excision had the highest mean abundance, while those involved in stability/transfer/defense had the lowest. The abundance of MGEs was significantly higher in the eastern population compared to the western population. Moreover, MGE abundance was positively correlated with regional GDP per capita and with ARG abundance within individuals.DiscussionOur findings suggest that socioeconomic development and industrialization are associated with increased MGE abundance in the human gut microbiome, which may in turn facilitate the spread of ARGs. These results highlight a potential unintended consequence of economic advancement on public health through microbiome-mediated antibiotic resistance.